Development of Faculty and Student Competencies in Digital Literacy for Arabic Language Learning - Ma’arif, A. Samsul; Suroiyah, Evi Nurus; Hikmawati, Sholihatul Atik; A’yun, Qurroti (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The digital era necessitates a paradigm shift in Arabic language education within higher education institutions. Traditional pedagogical methods are no longer sufficient to meet the demands of technologically driven learning environments. Digital literacy—encompassing the ability to effectively use, evaluate, and create digital content—has become a fundamental competency for both lecturers and students to achieve optimal learning outcomes. This empirical–conceptual study aims to analyze strategies for developing digital literacy competencies in Arabic language teaching, drawing from studies indexed in Scopus and SINTA between 2019 and 2025. The findings reveal that the effectiveness of digital-based Arabic language learning largely depends on two critical factors: the lecturers’ proficiency in designing interactive and engaging digital learning content, and students’ ability to manage online learning resources effectively. Lecturers are expected to integrate innovative digital tools, such as Learning Management Systems (LMS), multimedia platforms, and interactive applications, to foster dynamic and student-centered learning experiences. Meanwhile, students need to develop skills in digital resource management, online collaboration, and critical evaluation of information to become autonomous learners. Furthermore, the study emphasizes the importance of continuous professional development in digital literacy through systematic training programs, interdisciplinary research collaborations, and the contextual adaptation of digital media to pedagogical goals. By integrating technology into language instruction, educators can enhance communicative competence, creativity, and intercultural awareness among learners. Ultimately, strengthening digital literacy in Arabic language education not only enhances teaching and learning effectiveness but also prepares graduates to thrive in the globalized digital landscape.